How the images coincide – and the mind differs: Mainstream results from a Keynesian (?) textbook model - Bartel, Rainer (Momentum Quarterly, 2014)
Here, the economic mainstream (orthodoxy) and its alternatives (heterodoxy) are crudely broken down into Neoclassics and Keynesianism and contrasted. We start from the cognitive dissonance between mainstream theory and the economic system reality. There are broadly used macroeconomics textbooks that are deemed to be progressive in that they have been founded on Keynesianism. I consider such a model: the one by Blanchard et al. (2010) which I term the Blanchard Model. After a characterisation, I compare the neoclassical labour market model and its implications for the real sector with Keynes’s model of the goods market and its consequences for the labour market. Eventually, the pretence of the Blanchard Model of being progressive is evaluated and assessed. The Blanchard Model turns out to be formulated in a way substantially similar with the neoclassical model of equilibrium and can be seen as compatible with the Neoclassical Synthesis. After drawing some conclusions, an outlook is given on prospective developments of macroeconomics.
Keywords: Mainstream; Keynesianism; Neoclassical Synthesis; equilibrium concept; macroeconomics perspectives